The Berenstain bears and the sitter - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1981)
Brother and Sister Bear are not happy with the idea of Mrs. Grizzle for a baby-sitter, but they find her drawstring bag very intriguing.
Keywords: Babysitters -- Fiction; Bears -- Fiction